HORSETAIL PLANT PHYTOREMEDIATION POTENTIAL IN THE DECREASE OF HEAVY METAL IRON (Fe) IN LEACHATE AT CILOWONG’S LANDFILL AREA SERANG CITY - Fitri Dwirani; Ade Ariesmayana; Agung Sudrajad; Irvan Nurhakim; Deni Ihwanudin Firdaus (Universitas Trisakti, 2019)
Aim: This study aims to determine the potency of horsetail plant to remove heavy metal concentration. Methodology and Results: Data was obtained from fifty-four (54) horsetails which were divided into three batches of 12, 18, and 24 plants respectively. Furthermore, the experimental method with the subsurface flow system treatment was used with two samplings for seven days. The results showed that the first, second and third batches gave a 6.83%, 10.28%, and 16.26% impact on reducing concentration of Fe respectively with an approximate average of 11%. Therefore, the detention time of the leachate constructed wetland reactors significantly reduced the Fe contaminant. Conclusion, significance, and impact of study: This research provides a solution to mitigate the environment by adopting the accumulator of Horsetail plants (Equisetem hyemale) in the constructed wetlands reactor experiment. From the three reactors approximately 0.03 mg/L of heavy metal iron was removed after a seven day run. Therefore, horsetail plant showed a positive impact in reducing environmental pollution, a trend adoptable in wastewater and leachate treatment technology in Indonesia.